Perancangan Sistem Pengambilan Keputusan di dalam Pemberian Bantuan Alat Kepada Industri Kecil Menengah (IKM) Disperindagkop Kabupaten Aceh Tamiang - Dewiyana Dewiyana; Yusri Nadya; Dessi Supraptini (Jurnal Optimalisasi, 2016)
IKM selection process was conducted by comparing the GAP method is the difference between IKM indicator with standart value citeria indicator that given value. The results obtained from the determination of the selection criteria used eight criteria of product, price, place, promotion, process, people, physical environment, productivity and quality. A model that is designed to help decision making process in granting the aid DISPERINDAGKOP evenly. Based on the calculation results proved that the system has been designed to provide recommendation on IKM which can be selected as recipient of aid.Keywords: Election IKM, GAP Method, Decision Making System